Comparison on the Effectiveness of Postpartum Exercise And Oxytocin Massage for Uterine Involution of Postpartum Women in Kebumen, Indonesia - Kusumastuti Kusumastuti; Siti Mutoharoh; Wulan Rahmadhani (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Maternal mortality rates are caused by several factors, including bleeding. During postpartum, bleeding can be caused by a failure of uterine involution which can cause subinvolution. Oxytocin plays an important role in the uterine involution process. This study aims to compare the effectiveness of postpartum exercise and oxytocin massage for the uterine involution of postpartum women in the Kebumen. This study applied a quasi-experimental design for comparing two treatments. It involved a total of 534 respondents with 267 respondents in each group. Each group received 10 minutes of intervention per day for 9 days. The data were collected through observation sheets. The univariate analysis used frequency distribution and bivariate analysis used an independent t-test. The statistics show that the p-value (0.002) was lower than (0.05) meaning that the postpartum exercise and oxytocin massage provide different uterine involution times. The mean of uterine involution for the postpartum exercise group decreases by 137.60 hours compared to the oxytocin massage group by 159.06 hours. Postpartum exercise can be applied in post-natal care as it can make uterine involution faster. Abstrak: Kematian ibu di sebabkan beberapa factor termasuk perdarahan. Selama postpartum perdarahan di sebabkan oleh kegagalan involusi uterus yang di sebabkan oleh subinvolusi. Oxitosin memaikan peran yang sangat penting dalam proses involusi uteri. Penelitian ini bertujuan adalah untuk membandingkan efektifitas dari senam nifas dan pijat oksitosin terhadap proses involusi uteri paa ibu postpartum di wilayah kerja Kebumen. Metode quasi experiment di gunakan dalam penelitian ini dengan membandingkan dua treatment. Sampel pada penelitian ini berjumlah 534 dengan masing-masing 267 respondent pada masing-masing kelompok. Analisis univariate menggunakan distribusi frekuensi dan analisis bivariate menggunakan independent t-test. Hasil pada penelitian ini di temukan bahwa p-value (0.002) kurang dari 0.05 yang mana terddapat perbedaan antara senam nifas dan pijat oksitosin terhadap perubahan involusi uteri. Mean dari involusi uteri pada grup senam nidas menurun menjadi 137.60 jam di banding dengan pijat oksitosin grup dengan 159.06 jam. Senam nifas bisa di jadikan atau di aplikasikan dalam perawatan pascapersalinan karena dar hasil dapat membuat dan membantu involusi uteri lebih cepat pada ibu nifas.